2008
DOI: 10.1590/s0100-67622008000300014
|View full text |Cite
|
Sign up to set email alerts
|

Análise termogravimétrica da pirólise da acácia-negra (Acacia mearnsii de Wild.) cultivada no Rio Grande do Sul, Brasil

Abstract: RESUMO -Este trabalho reporta um estudo experimental que objetivou a investigação dos efeitos da temperatura, da taxa de aquecimento e do tempo na eficiência e nos parâmetros cinéticos da decomposição da madeira de acácia-negra (Acacia mearnsii De Wild.) plantada no Rio Grande do Sul. O processo da pirólise da acácia-negra foi investigado por análise termogravimétrica (TGA), e os parâmetros cinéticos foram obtidos a partir de ensaios dinâmicos e isotérmicos. Os ensaios dinâmicos foram conduzidos desde a temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
0
5
0
8
Order By: Relevance
“…The results indicate that particleboards processed at 130°C using twocomponent castor oil based resin and Tauari wood particles have a promising potential to be classified as high density particleboards indicated for commercial and industrial applications 28 . The mean values of modulus of elasticity (MOE) of the particleboards (Table 2) did not reach the minimum value (2750 MPa) recommended by the A208-1-1999 standard 44 in any of the treatments, and the MOE value obtained at 130°C (2378.5 MPa) was 15.62% lower than that recommended by the aforementioned standard; however, all the values exceeded those recommended by the EN 312:2010 standard. Several researchers have reported low MOE values 16,26,30,41 , attributing this behavior to poor distribution of the adhesive during the compression of particleboards.…”
Section: Physical Characterization Of the Particleboardsmentioning
confidence: 85%
See 2 more Smart Citations
“…The results indicate that particleboards processed at 130°C using twocomponent castor oil based resin and Tauari wood particles have a promising potential to be classified as high density particleboards indicated for commercial and industrial applications 28 . The mean values of modulus of elasticity (MOE) of the particleboards (Table 2) did not reach the minimum value (2750 MPa) recommended by the A208-1-1999 standard 44 in any of the treatments, and the MOE value obtained at 130°C (2378.5 MPa) was 15.62% lower than that recommended by the aforementioned standard; however, all the values exceeded those recommended by the EN 312:2010 standard. Several researchers have reported low MOE values 16,26,30,41 , attributing this behavior to poor distribution of the adhesive during the compression of particleboards.…”
Section: Physical Characterization Of the Particleboardsmentioning
confidence: 85%
“…As for thickness swelling, the IB test results shown in Table 2 demonstrate that, regardless of the processing temperature, the mean values of this property varied from 1.55 to 1.70 MPa, which are higher than those recommended by the NBR 14810-2, A208.1:1999, and EN 312:2010 standards 43,44,47 . The mean values of IB showed no statistically significant differences at a 5% level of probability and are in agreement with those reported by Iwakiri et al 32 for Tauri wood.…”
Section: Mechanical Characterization Of the Particleboardsmentioning
confidence: 86%
See 1 more Smart Citation
“…25,26 A peak in the range 400-500 °C, which was only observed for MB, was attributed to the loss of lignin. Riegel et al 27 evaluated the use of different heating rates for pyrolysis of black wattle cultivated in Rio Grande do Sul. It was concluded that lignin degradation across a broad temperature range could lead to the non-appearance or overlapping of peaks during pyrolysis of the cellulosic material.…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 99%
“…Esse processo resulta em um conjunto de pequenas espécies moleculares, as quais são relacionadas à composição da matéria prima original (Riegel et al, 2008). Na pirólise, os polímeros lignocelulósicos (hemicelulose, celulose e lignina) são submetidos à clivagem térmica para produzir diferentes componentes químicos que rapidamente vaporizam-se e após condensação tem-se um líquido negro chamado de bio-óleo (Lu et al, 2011a).…”
Section: Introductionunclassified